E-cigarettes—An unintended illicit drug delivery system. (1st November 2018) - Breitbarth, Andreas K.; Morgan, Jody; Jones, Alison L.
Highlights: E-cigarettes are a new route of administration for a range of illicit drugs. This information is not well-reflected in the scientific literature. Most drugs examined had evidence of use in illicit drug forums. This presents both a population health risk and a management issue for clinicians. Abstract: Since the introduction of electronic cigarettes (e-cigarettes) in 2003, the technology has advanced allowing for greater user modifications, with users now able to control voltage, battery power, and constituents of the e-cigarette liquid. E-cigarettes have been the subject of a growing body of research with most research justifiably focused on the chemical makeup and risk analysis of chemicals, metals, and particulates found in e-cigarette liquids and vapor. Little research to date has focused on assessing the risks associated with the drug delivery unit itself and its potential for use as an illicit drug delivery system. In light of this, a range of illicit drugs was researched focusing on pharmacodynamics, usual method of administration, the dosage required for toxicity, toxic effects, and evidence of existing use in e-cigarettes in both literature and online illicit drug forums. A systematic literature search found evidence of current use of e-cigarettes to vape almost all illicit drug types analyzed. This presents both a potential population health risk and a management issue for clinicians. It also raises the issue of policing illicit drugs due to potential altered characteristic smells and storage within e-cigarette fluids. E-cigarettes are a viable illicit drug delivery system with evidence both inside and outside of the formal medical literature detailing their potential use for drug delivery of a wide range of illicit and legal drugs.